Методика построения ориентировочной основы действий при решении задач с параметрами - Romanov P. I., Romanova T. E. (Scientific studies from theory to practice, 2016)
The article is devoted to methods of teaching school students solving problems with parameters. Based on the analysis of the activities and the theory of the gradual formation of mental actions together with the students revealed a sequence of operations in the search for the necessary conditions. The identified sequence is the orienting basis of action for solving problems with parameters.
Keywords: задачи с параметром; ориентировочная основа действий; Problem with a parameter; indicative for the action; the necessary and sufficient conditions; необходимые условия; достаточные условия